Mouse Spexin: (I) NMR Solution Structure, Docking Models for Receptor Binding, and Histological Expression at Tissue Level - Wong, Matthew K. H.; He, Mulan; Sze, Kong Hung; Huang, Tao; Ko, Wendy K. W.; Bian, Zhao-Xiang; Wong, Anderson O. L. (Frontiers in Endocrinology, 2021)
Spexin (SPX), a highly conserved neuropeptide, is known to have diverse functions and has been implicated/associated with pathological conditions, including obesity, diabetes, anorexia nervosa, and anxiety/mood disorders. Although most of the studies on SPX involved the mouse model, the solution structure of mouse SPX, structural aspects for SPX binding with its receptors GalR2/3, and its cellular expression/distribution in mouse tissues are largely unknown. Using CD and NMR spectroscopies, the solution structure of mouse SPX was shown to be in the form of a helical peptide with a random coil from Asn1 to Pro4 in the N-terminal followed by an α-helix from Gln5 to Gln14 in the C-terminus. The molecular surface of mouse SPX is largely hydrophobic with Lys11 as the only charged residue in the α-helix. Based on the NMR structure obtained, docking models of SPX binding with mouse GalR2 and GalR3 were constructed by homology modeling and MD simulation. The models deduced reveal that the amino acids in SPX, especially Asn1, Leu8, and Leu10, could interact with specific residues in ECL1&2 and TMD2&7 of GalR2 and GalR3 by H-bonding/hydrophobic interactions, which provides the structural evidence to support the idea that the two receptors can act as the cognate receptors for SPX. For tissue distribution of SPX, RT-PCR based on 28 tissues/organs harvested from the mouse demonstrated that SPX was ubiquitously expressed at the tissue level with notable signals detected in the brain, GI tract, liver, gonad, and adrenal gland. Using immunohistochemical staining, protein signals of SPX could be located in the liver, pancreas, white adipose tissue, muscle, stomach, kidney, spleen, gonad, adrenal, and hypothalamo-pituitary axis in a cell type-specific manner. Our results, as a whole, not only can provide the structural information for ligand/receptor interaction for SPX but also establish the anatomical basis for our on-going studies to examine the physiological functions of SPX in the mouse model.